OPTIMATION OF STRAIGHT BLADE DARRIEUS TURBINE USING AS HYDRO TURBINE - ROSIADI (NIM: 23107010), JEFRI
Straight Blade Darrieus Turbine is one of Vertical Axis Turbine type which usually used in wind turbine. In this research the turbine is used as hydro turbine. Since the density of water greater than the air. The turbine is operated with extremely low head, just using kinetic energy from flowing water. This turbine already tested and operates well. The turbine power can be optimized by adjust the pitch angle about 5 degree will produce 39.48 watt (Cp=0,115) speed 34,36 rpm with water velocity 1,32 m/s, runner radius 0.5 m, using 3 units blade NACA 0018,chord length 0,2 m, 0,3 m height. By fluent simulation with the same condition, the maximum power achieved 44,85 watt (Cp 0,13) at speed 30 rpm. Optimum solidity achieved at C/R = 0,33 and the maximum Cp = 0,168. Although the efficiency is too low, this turbine suitable for using in the river that doesnÃ‚Â’t have high head. Other advantages of this turbine are easy to made, not necessary a dam and penstock that cause of high cost.